Asuhan Keperawatan pada Anak A dengan Acute Kidney Injury (AKI) di Ruang PICU Rumah Sakit Umum Daerah Banda Aceh (IJM: Journal of Multidisiplinary, 2025)
The incidence rate of Acute Kidney Injury (AKI) has increased significantly year by year. Additionally AKI can suffer in children, if it is not treated immediately it will cause several complications, including disrupting the function of organs such as the brain, heart and lungs. In this study, it aimed to expound nursing care for a child with Acute Kidney Injury (AKI) in the PICU ward. The design of this research is a case study. The results of the assessment indicated that the patient haddecreased consciousness, nausea, vomiting, malnutrition, and electrolyte imbalance. Moreover, nursing problems included impaired gas exchange, hypervolemia, ineffective peripheral perfusion, risk of ineffective renal perfusion, risk of electrolyte imbalance, risk of nutritional deficit and risk of aspiration. The implementations accomplished weremonitoring shock prevention, hypervolemia management, circulation care, electrolyte monitoring, nutritional management, respiration monitoring, prevention of aspiration and administration of drug therapy.  The results of the nursing evaluation during four days of treatment showed that the problem of gas exchange disorders was partially resolved, the problem of hypervolemia was partially resolved, the problem of ineffective peripheral perfusion was partially resolved, the problem of the risk of ineffective renal perfusion was partially resolved, the problem of the risk of electrolyte imbalance was partially resolved, the problem of the risk of nutritional deficit was not resolved, the problem of the risk of aspiration was partially resolved. It is also recommended that nurses in providing nursing care to children should emphasize more on atraumatic care and take into account every action taken to prevent the risk of trauma to children and families when providing nursing actions.